Hypertriglyceridemia-Induced Acute Pancreatitis Secondary to Glycogen Storage Disease Type Ia: Successful Treatment With Plasmapheresis - Ethan K. Overfelt; S. Bryan Jones; Scott D. Bieber; David C. Pfeiffer (Annals of Internal Medicine: Clinical Cases)
Glycogen storage disease type Ia (GSD-Ia) is a rare autosomal recessive disorder caused by a loss-of-function mutation in glucose-6-phosphatase, resulting in recurrent fasting hypoglycemia. This leads to several systemic metabolic complications, including hypercholesterolemia and hypertriglyceridemia, which can induce acute pancreatitis episodes. We report on using early plasmapheresis in addition to oral fibrate therapy as a successful treatment of a 27-year-old GSD-Ia patient with hypertriglyceridemia-induced acute pancreatitis. Plasmapheresis was initiated the day after admission and continued daily for three treatments, ultimately resulting in a seven-day admission.